PENGARUH KEPUASAN DAN LOYALITAS KONSUMEN TERHADAP PENINGKATAN PENJUALAN DI MEDIA SOSIAL (STUDI KASUS PADA KEDAS BEAUTY) - Damiyana, Damdam; Mulyanah, Mulyanah (JAB (Jurnal Akuntansi & Bisnis), 2021)
This study aims to find out how the influence of consumer satisfaction and loyalty on increasing sales on social media (a case study on Kedas Beauty). Consumer satisfaction and loyalty is very important in a business, especially a business with an online system. The current phenomenon is buying and selling online through social media with various conveniences offered. Satisfying consumers will lead to consumer loyalty, so the company can gain a wider market share and increase sales. The analysis technique used is multiple linear regression and hypothesis testing with a significance level of 5%. The results showed that consumer satisfaction and loyalty had a significant effect on increasing sales of Kedas Beauty on social media, which was 0.708. While the remaining 29.2% (100-70.8) was determined by other factors outside the model that were not detected in this study.Keywords: Consumer Satisfaction, Consumer Loyalty, Social Media